Locus of Control as a Mediator of Financial Knowledge and Income on Financial Management Behavior in Employees of PT. Poso Energy - Emy Amriani Asmin; Samsuri; Alfian Fathah Yasin (MultiTech Publisher, 2024)
This study aims to examine the influence of financial knowledge and income on financial management behavior through locus of control. The population consists of 150 individuals, with a sample size of 110 people, selected using the Slovin formula. Data collection methods include interviews, questionnaire completion, and observation. Data analysis employs path analysis with the help of SPSS software version 25.00. The results show that financial knowledge and income have a positive and significant effect on locus of control. Financial knowledge, income, and locus of control positively and significantly affect financial management behavior. Financial knowledge and income also have a positive and significant impact on financial management behavior through locus of control.